Yield, Quality, Antioxidants, and Mineral Composition of Traditional Italian Storage Onion Cultivars in Response to Protein Hydrolysate and Microalgae Biostimulation - Alessio Vincenzo Tallarita; Otilia Cristina Murariu; Tomas Kopta; Florin Daniel Lipșa; Leonardo Gomez; Eugenio Cozzolino; Pasquale Lombardi; Silvio Russo; Gianluca Caruso (Horticulturae)
Increasing interest is being devoted to environmentally friendly strategies, such as the use of plant biostimulants, to enhance crop performance and concurrently ensure food security under the perspective of sustainable management. The effects of two biostimulant formulations (protein hydrolysate and spirulina) on four Italian traditional storage onion cultivars (Ramata di Montoro, Rossa di Tropea, Rocca Bruna, Dorata di Parma) were investigated in Naples province (southern Italy), in terms of yield, quality, shelf-life, bioactive compounds, and mineral composition. Ramata di Montoro showed the highest levels of yield (66.4 t ha−1) and vitamin C (31.5 mg g−1 d.w.) and the longest shelf-life (228 days). Significant increases in marketable yield were recorded under the applications of both protein hydrolysate (+15.5%) and spirulina (+12.4%) compared to the untreated control. The two biostimulant formulations significantly increased bulb shelf-life and the contents of polyphenols (201.4 mg gallic acid eq. 100 g−1 d.w. on average vs. 158.6 of the untreated control), vitamin C (26.8 mg g−1 d.w. on average vs. 22), and both lipophilic and hydrophilic antioxidant activities. These findings demonstrate the effectiveness of both protein hydrolysate and spirulina as sustainable tools for enhancing both yield and quality parameters within the frame of environmentally friendly farming management.